Pengaruh Latihan Beban Karet Terhadap Kecepatan Tendangan Dollyo Chagi Pada Atlet Junior Taekwondo Unit SMP Xaverius Kuala Tungkal - Rasyono Rasyono (Journal Sport Area, 2018)
This study aimed to determine the effect of rubber load exercise on improving the speed of dollyochagikicks for junior taekwondo athletes at Junior High School (SMP) Xaverius Kuala Tungkal. The populationsof this study were 46junior taekwondo athletes from the unit of Junior High School (SMP) Xaverius, Kuala Tungkal. From those populations, 11 students were selected as the samples by purposive sampling technique. The results of t-test data analysis show that with α = 0.05 and degrees of freedom (n-1) = 10,the value of tcounted obtained in this study was10.27, and the value of t table was 1.812. As a result, tcounted > t table (10.27> 1.812). This implies that Ha hypothesis is accepted and Ho hypothesis is rejected. Hence, from the data analysis and hypothesis testing, it can be concluded that rubber weight exercisesignificantly influences the improvement of the speed of dollyochagikids for junior taekwondo athletesat the unit of Junior High School (SMP) Xaverius Kuala Tungkal.